A study to determine the prevalence of urinary incontinence in antenatal women at a tertiary care centre in central India - Joshi, Deepa; Achale, Sheetal; Dalal, Nilesh; Patel, Alka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Urinary incontinence is a common condition in pregnancy and postpartum. There are more than a thousand articles on urinary incontinence (UI) in pregnancy but very limited literature from Indian subcontinent is available. Incidence and prevalence figures of UI in association with pregnancy vary substantially. Not many reviews have focused solely on incidence and prevalence of UI in association with pregnancy. Prevalence of UI in pregnancy ranges from 32% to 64%. Methods: A cross sectional observational study was conducted in the department of obstetrics and gynecology, MGM Medical College and M.Y. Hospital, Indore over the period of 6 months on 1000 pregnant women who were following antenatal care (ANC) clinic. Pregnant women, who were severely sick, diagnosed with kidney or urinary infection and vaginal infections women were excluded from the study. The data were collected using a structured questionnaire. After the purpose of the study was explained, written consent was obtained from each voluntary participant. This study was approved by institutional ethical committee. The data was recorded in predesign coded case report form and statistical analysis was performed using the STATA 12.1. Results: In the present study the prevalence of urinary incontinence reported is 16.4% of women during pregnancy. Conclusions: In this study the prevalence of UI during current pregnancy was found to be lower compared to previous studies conducted. The previous history of surgery, constipation, obesity and respiratory problems were found to be significantly associated with UI during pregnancy.